Fuzzy logic based behaviors blending for intelligent reactive navigation of walking robot - Al-Jumaily, Adel Ali S.; Amin, Shamsudin H. M. (1999)

(untitled)
The reaction of an autonomous mobile robot to dynamic, uncertain, and changeable environments is one of most difficult issues in control of intelligent autonomous robot movement. Fuzzy control appears as a very useful tool for handling intelligent reactive navigation. The present work deals with building of fuzzy behavior based reactive navigation for obstacle avoidance, and proposes a method to blend and coordinate multi-behaviors at the same time. This method using a fuzzy technique and fixed priority value to reflect the importance of the behavior. We have built our simulation and animation programs that can reflect online the robot movement using a graphical user interface